Jaw deformities in the larvae of yellowtail kingfish (Seriola lalandi Valenciennes, 1833) from two groups of broodstock - Ma, Zhenhua; Tan, Daniel Aik Yang; Qin, Jian G. (Indian Journal of Fisheries, 2014)
Jaw malformation is a major bottleneck in hatchery development of marine finfish. This study compared the occurrence of jaw deformities in larvae produced from two sets of broodstock of yellowtail kingfish (Seriola lalandi, Valenciennes 1833). Fish eggs from two groups of broodstock (B1 and B2) were separately hatched and the fish larvae were reared up to 25 days under similar conditions. No significant differences were found in specific growth rate and overall jaw deformities between these two groups. However, a clear pattern was observed in occurence of jaw deformities at different lengths groups. In population B1, minor deformities occurred in larvae of 9.80-11.60 mm standard length (SL) with maximum in fish of 10.89-11.11 mm SL. In B2, minor jaw deformities occurred in larvae of 8.69-12.21 mm SL with maximum deformities observed in fish of 9.35-9.52 mm SL and 10.18-10.34 mm SL. No severe jaw deformities were found in either of the two groups of larvae in this study. The study clearly showed that the sizes at which jaw deformities occur vary between two groups of larvae of the same species, under the same environmental and nutritional conditions. which indicated the need for selective breeding to reduce occurrence of deformity in the larvae.